2014
DOI: 10.1128/jvi.01582-14
|View full text |Cite
|
Sign up to set email alerts
|

Seed Sequence-Matched Controls Reveal Limitations of Small Interfering RNA Knockdown in Functional and Structural Studies of Hepatitis C Virus NS5A-MOBKL1B Interaction

Abstract: Hepatitis C virus (HCV) is a widespread human pathogen causing liver cirrhosis and cancer. Similar to the case for other viruses, HCV depends on host and viral factors to complete its life cycle. We used proteomic and yeast two-hybrid approaches to elucidate host factors involved in HCV nonstructural protein NS5A function and found that MOBKL1B interacts with NS5A. Initial experiments with small interfering RNA (siRNA) knockdown suggesting a role in HCV replication led us to examine the interaction using bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Since TRIM25 -targeting siRNA #3 was most efficient at rescuing SINV Toto1101/Luc replication, we designed and tested an additional C911 control. The 9 th to 11 th nucleotides of the siRNA were mutated to their complementary sequence, hence the designation C911, to rule out the possibility that the knockdown phenotype was due to the off-target effects of the siRNA [29, 30]. The C911 control should lose its siRNA activity but still maintain its off-target effects as a microRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Since TRIM25 -targeting siRNA #3 was most efficient at rescuing SINV Toto1101/Luc replication, we designed and tested an additional C911 control. The 9 th to 11 th nucleotides of the siRNA were mutated to their complementary sequence, hence the designation C911, to rule out the possibility that the knockdown phenotype was due to the off-target effects of the siRNA [29, 30]. The C911 control should lose its siRNA activity but still maintain its off-target effects as a microRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Huh-7.5 or Huh-7.5 CD81 low cells were transfected with viral RNA as previously described (47). Transfection efficiency was enhanced by centrifugation at 2000 rpm, 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…First, we designed two siRNAs targeting Siglec1 (siR-NA#1 and #2) and determined their knockdown efficiency ( Figure 2A). Both irrelevant (NC) and recently reported C911 seed-matched negative-control siRNA were used to exclude the potential off-target effects of RNA interference [21] (Figure 2A). By measuring the VSV RNA level in the cytoplasm and the 50% tissue culture infective dose (TCID 50 ) per milliliter of the supernatant from the infected macrophages, we found that Siglec1 knockdown suppressed VSV replication ( Figure 2B-2C).…”
Section: Siglec1 Promotes Vsv Replication Through Inhibiting Virus-trmentioning
confidence: 99%